Experimental investigation of double corrugated steel plate shear walls. (March 2022) - Ghodratian-Kashan, S.M.; Maleki, S.
Abstract: In this research, the cyclic performance of double corrugated steel plate shear walls (DCSPSWs) is investigated experimentally and confirmed numerically. Three half-scale one-story single-bay specimens with different infill plate designs were constructed and tested under lateral cyclic loads. The design parameters examined were the connection between the corrugated plates and the connection between the infill plate and the columns. The results showed that regardless of the infill plate design, the DCSPSWs had a spindle-shaped hysteresis curve with good cyclic performance. However, the beam-only-connected DCSPSW exhibited slightly lower lateral load resistance. Finite element (FE) models of the specimens were developed and the outcome of analyses were compared to that of the experimental tests. The beam-only-connected DCSPSW showed a reduction in column axial load. Highlights: Three double corrugated steel plate shear walls were tested under cyclic loading. Specimen 1 had the corrugated plates attached to each other and also to the columns. Specimen2 had the two corrugated plates detached from each other. Specimen 3 had the corrugated plates detached from the columns. Nonlinear finite element analysis was utilized to confirm the test results and validate modeling technique. Specimens 1 and 2 had similar performance under cyclic loads. Specimen 3 had a lower capacity but reduced the columns axial demand.